2021
DOI: 10.1002/app.52019
|View full text |Cite
|
Sign up to set email alerts
|

Lignin demethylation for modifying halloysite nanotubes towards robust phenolic foams with excellent thermal insulation and flame retardancy

Abstract: The demethylation of lignin was conducted under HBr catalysis and microwave irradiation resulting in a demethylation rate of 21.4% as calculated from 1 H NMR. The demethylated lignin (DL) was applied to modify halloysite nanotubes (HNTs) forming a nano-hybrid containing 16.5 wt% of DL according to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[44] Lignin prepared by this method is a suitable substitute for phenol in ligninbased PF resin adhesives. Demethylation can be performed using various methods with different catalysts, such as SO 3 2À (Scheme 3a), [45] HBr (Scheme 3b), [46] and a combination of 1dodecanethiol, hydroiodic acid, and iodocyclohexane (Scheme 3c). [47] The specific method used depends on the lignin type and desired properties of the modified lignin when considered as a substitute for the preparation of PF resin adhesives.…”
Section: Demethylation Modification Of Ligninmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] Lignin prepared by this method is a suitable substitute for phenol in ligninbased PF resin adhesives. Demethylation can be performed using various methods with different catalysts, such as SO 3 2À (Scheme 3a), [45] HBr (Scheme 3b), [46] and a combination of 1dodecanethiol, hydroiodic acid, and iodocyclohexane (Scheme 3c). [47] The specific method used depends on the lignin type and desired properties of the modified lignin when considered as a substitute for the preparation of PF resin adhesives.…”
Section: Demethylation Modification Of Ligninmentioning
confidence: 99%
“…[45] Copyright (2016), with permission from RSC Publishing; (b) HBr, reproduced from Ref. [46] Copyright (2021), with permission from John Wiley and Sons; (c) combination of 1-dodecanethiol, hydroiodic acid, and iodocyclohexane, reproduced from Ref. [47] Copyright (2017), with permission from American Chemical Society.…”
Section: Phenolation Modification Of Ligninmentioning
confidence: 99%
“…Lignin demethylation over halogen acids (HI, HBr) is also used to increase the hydroxyl content of lignin with the intent to improve lignin reactivity. [134][135][136] Wang et al used HBr and HI as the nucleophilic reagents for lignin demethylation. The results showed that the molar amounts of phenolic hydroxyls increased to 0.67 mmol g −1 for the HI-DL (demethylated lignin), and 0.64 mmol g −1 for the HBr-DL, from 0.52 mmol g −1 for the initial lignin.…”
Section: Synthesis Of Lpr From Modified Ligninmentioning
confidence: 99%
“…Li et al [192] produced BPF foams using demethylated lignin (DL) modified with halloysite nanotubes (HNTs). Initially, lignin was demethylated in the presence of HBr and other solvents in a microwave reactor at 90 °C for 90 min.…”
Section: Synthesis Of Biobased Phenol Formaldehyde Foamsmentioning
confidence: 99%
“…4) via high-speed mechanical stirrer. The resulting mixture was kept at 80 °C for 75 min to cure to obtain the final foam [192].…”
Section: Synthesis Of Biobased Phenol Formaldehyde Foamsmentioning
confidence: 99%